Electrolyte disorders in advanced non-small cell lung cancer patients treated with immune check-point inhibitors: A systematic review and meta-analysis. (July 2020) - Cantini, Luca; Merloni, Filippo; Rinaldi, Silvia; Lenci, Edoardo; Marcantognini, Giulia; Meletani, Tania; Fiordoliva, Ilaria; Morgese, Francesca; Torniai, Mariangela; Ricci, Giulia; Giampieri, Riccardo; Berardi, Rossana
Abstract: Background: Aim of this meta-analysis was to determine the relative risk (RR) of electrolyte disorders (EDs) in advanced non-small cell lung cancer (aNSCLC) patients treated with immune check-point inhibitors (ICIs). Methods: We searched for phase II/III randomized controlled trials (RCTs) comparing ICIs (alone or combined with chemotherapy) with standard chemotherapy in aNSCLC. Summary incidence and RR were calculated. Results: Six RCTs with data on all-grade hyponatremia were identified (n = 3257). The incidence was 8.7 % in the study group and 4.9 % in the control group (RR 1.78, 95 %CI 1.12–2.80). Looking at all-grade hypokalemia, 7 RCTs were included (n = 4119). Incidence was 10.4 % in ICIs-treated patients and 5.9 % in the control arms (RR 1.62, 95 % CI 1.30–2.02). Conclusions: Treatment with ICIs in aNSCLC is associated with a significant increased risk of hyponatremia and hypokalemia compared to chemotherapy. Monitoring of electrolyte levels should be emphasized in this setting.